Collective intentionality or documentality?. (May 2015) - Ferraris, Maurizio
In this article I defend two theses. The first is that the centrality of recording in the social world is manifested through the production of documents, a phenomenon which has been present since the earliest phases of society and which has undergone an exponential growth through the technological developments of the last decades (computers, tablets, smartphones). The second is that the centrality of documents leads to a view of normativity according to which human beings are primarily passive receptors of rules manifested through documents. We are not intentional producers of values. The latter, as I shall suggest in my conclusion, should be viewed as being 'socially dependent' rather than 'socially constructed'.